Magical Realism as Subversion: Reimagining Reality and Uncovering the Truth in Murakami’s 1Q84 and Obreht’s The Tiger’s Wife - Sharma, Khum Prasad (Molung Educational Frontier, 2026)
Magical realism has long been celebrated as a disruptive narrative mode capable of blending the extraordinary with the ordinary. While often associated with twentieth-century Latin American and postcolonial contexts, its evolution in the twenty-first century reflects a broader, global application. This study examines how Haruki Murakami’s 1Q84 (2010) and Tea Obreht’s The Tiger’s Wife (2011) reimagine reality through the lens of magical realism. The aim of the study is to investigate how these narratives employ irreducible magical elements to engage with pressing social and personal concerns—urban alienation, religious extremism, and historical trauma. Methodologically, the research draws on Wendy B. Faris’s theoretical framework from Ordinary Enchantments (2004) that focuses on her concept of “irreducible elements.” The analysis finds that 1Q84 uses parallel worlds and subtle supernatural disruptions to explore the fragility of truth and the redemptive potential of human connection in a hypermodern society. Similarly, The Tiger’s Wife interweaves myth, folklore, and war memory to articulate the persistence of cultural storytelling as a form of resilience. By placing these novels in comparative dialogue, the article demonstrates that magical realism continues to operate as a globally resonant mode capable of reimagining reality, preserving marginalized forms of knowledge, and resisting reductive historical narratives. The study’s original contribution lies in showing how contemporary magical realism functions as a shared aesthetic of ontological questioning and cultural resilience across disparate literary traditions.